Hisab Hakiki Model Muhammad Wardan: Sebuah Penelusuran Awal - Azhari, Susiknan (Al-Jamiah Research Centre, 2004)
This article tries to study about calculation (á¸¥isÄb) model developed by Muhammad Wardan to formulate a National Hijriyah Calendar. Muhammad Wardan is one of the designer of the concept of wujÅ«dul hilÄl. This concept was built by combining normative and empirical level (middle way) between the system of hisab ijtima qabla al-ghurÅ«b and imkÄn al-ruyah. This combination was also named as middle way between pure hisab and pure rukyat. Due to this type of concept, be renewal thought of Mubammad Wardan to decide the beginning of Qamariyah month was quite original at that time. Therefore, Wardans theory of wujudÅ«l hilÄl is still used until nowadays especially by Muhammadiyah people. However, it is significant to note that the thought of Wardan does not perfectly answer Â the problem of National Hijriyah Calendar, I.e., to decide the Westest and Eastest Â points of a region or country to start or end the month of Ramadlan.